Retracted article: Towards Constructing an Integrated Model for the Cognitive System: Revisiting Semantic Networks - Armin Ehsani; Hussein Kareshki; Imanollah Bigdeli (Cognitive Studies | Études cognitives, 2021)
This is a retracted article, whose corrected version, bearing the same title, is available under the DOI: https://doi.org/10.11649/cs.2910. Following the authors' request, the incorrect spelling of the name of one of them (Hussein → Hossein) and the incorrect name of the university they are affiliated with were corrected.